Impelementasi Metode N-Hash Untuk Mendeteksi Keaslian File Audio - Udiyani (Journal of Informatics Management and Information Technology, 2022)
Audio file is a means of information from one person to another or from a group to another. The development of computerized technology has greatly increased. Audio files are very vulnerable to fraud, eavesdropping or data theft by irresponsible parties. In order to maintain the security of audio files, it can be done by using cryptographic techniques. Cryptography is a collection of techniques that are useful for securing information. Apart from securing information, it also maintains the confidentiality and integrity of the information. Cryptography is used for important communications such as communications among the military, diplomats, and spies. But nowadays cryptography is more non-repudiation.N-Hash is a family of encryption algorithms designed to have an efficient and simple software implementation on 128-bit microprocessors. The original member of this family is called N-hash which has 8 rounds